Propriedades bioativas de pães de fermentação natural inoculados com Companilactobacillus paralimentarius 41, Lactiplantibacillus plantarum 47 E Levilactobacillus brevis 83 - Rodrigues, Tatiana Zanella (2025)
This study aimed to develop sourdough, and breads inoculated with autochthonous starter cultures and analyze their physicochemical and functional properties. Three formulations of sourdough, and breads inoculated with Companilactobacillus paralimentarius 41 (Cp41), Lactiplantibacillus plantarum 47 (Lp47), and Levilactobacillus brevis 83 (Lb83) were produced at three distinct fermentation times (2, 3, and 4 hours). A non-inoculated control formulation was established. The sourdough were evaluated for physicochemical parameters (pH, total acidity, and exopolysaccharide content) and microbiological parameters (enumeration of viable cells). The fermented doughs were enumerated, and the bread were analyzed for pH, total acidity, specific volume, in vitro protein digestibility, hydrolysis index (HI), estimated glycemic index (eGI), antioxidant activity, phenolic compound content, and sugar and organic acid composition. Repeated-measures factorial analysis of variance (ANOVA) followed by Tukey’s post hoc test (5% significance level), principal component analysis (PCA), and Pearson correlation analysis were performed. Both the sourdough, and sourdough bread exhibited a pH below 4.0 and acidity ranging from 8.9 to 9.32 g/100g. Lactic acid bacteria showed counts above 8 log CFU/g, while yeasts ranged between 6.60 and 8.48 log CFU/g in bread dough after fermentation. The sourdough inoculated with Lp47 exhibited the highest exopolysaccharide production (13.80 ± 1.35 g/kg). An increase in loaf specific volume was observed from 3 hours of fermentation bread (2,41-2,74 cm³/g) across all samples. Bread produced with Lp47 and Lb83 showed enhanced in vitro protein digestibility at 4 hours of fermentation (99.70 ± 0.01% and 99.30 ± 0.01%, respectively). The bread inoculated with Lb83 exhibited the lowest estimated glycemic index after 3 hours of fermentation (73.78 ± 0.91). Antioxidant activity increased during fermentation, with the bread inoculated with Lb83 presenting the highest phenolic compound content at 3 hours of fermentation (28.19 mg GAE/100 g ± 0.95). All sourdough bread exhibited a reduction in maltose, glucose, and fructose levels after 4 hours, along with an increase in lactic acid content throughout fermentation. Additionally, all samples showed a reduction in formic acid content between 2 and 4 hours of fermentation. The findings identified a positive correlation between loaf specific volume, and both phenolic compound content (r = 0.66, p < 0.05) and total acidity (r = 0.95, p < 0.001). Antioxidant activity (DPPH• method) also demonstrated a positive correlation with the eGI of inoculated samples. PCA analysis associated the bioactive characteristics, improved protein digestibility, and glycemic index with breads inoculated with Lp47 and Lb83. Both strains showed promising potential for sourdough applications, with an optimal fermentation time of 3 hours. Further studies are needed to better understand strain interactions and technological properties, aiming for commercial application and functional benefits related to health and nutrition.